(untitled) (Nexo Revista Científica, 2021)
In this study, the effects of various geometric parameters of a dam in 2D static analysis of stress-strain on the upstream slope of the asphaltic concrete core rockfill dams were investigated. For this purpose, first the geometric characteristics of a large number of world’s dams were collected and assessed, then by geometric modeling of these dams, many numerical models were developed for static analysis using GeoStudio software in eight height classes, three cases of upstream and downstream slopes, three different shape and thickness of the asphaltic concrete core under different Impounding states including "Full Reservoir", "Half full Reservoir", "End of construction and "Rapid Drawdown on a rigid type of foundation. The results of this study demonstrated that in four different construction and impounding states and in three different cases of slopes, Increasing the height parameter, causes increasing the Maximum total stress, Maximum total strain, Shear strain and Maximum shear stress for all construction and impounding states. The Maximum total stress decreased for all operating situations as the upstream slope reduced. According to the obtained results from the static stress-strain analysis, increasing both vertical and inclined asphaltic concrete core thicknesses, leads to decreasing the Maximum shear stress in Full Reservoir state but it increases in other state of impoundment. Moreover, by comparing the displacements related to specified points on the upstream slopes, increasing the height parameter, leads to increasing both horizontal and vertical displacements, the volumetric strain, deviator strain and deviator stress for all impounding conditions. In the following, the additional results were provided along with diagrams for further analysis.